2017
DOI: 10.1016/j.jtumed.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of clinical, radiological and serum analysis of hypovitaminosis D with polycystic ovary syndrome: A systematic review and meta-analysis

Abstract: Objectives Vitamin D deficiency leads to a myriad of healthcare problems from cardiovascular, metabolic, endocrine, and neurological disorders to cancer. However, the role of vitamin D deficiency in the etiopathogenesis of polycystic ovary syndrome (PCOS) is unclear. This study aimed to measure objectively the impact of vitamin D deficiency on PCOS through a quantitative assessment of the existing literature. Methods We conducted a systematic search of published literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…They found that increased BMI had a significant negative effect on 25OHD, but didn’t support the association between PCOS on 25OHD ( 33 ). Some studies showed convincing data that low 25OHD levels were associated with obesity and IR, but not with PCOS per se ( 26 , 32 , 33 ), which was consistent with our outcome.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…They found that increased BMI had a significant negative effect on 25OHD, but didn’t support the association between PCOS on 25OHD ( 33 ). Some studies showed convincing data that low 25OHD levels were associated with obesity and IR, but not with PCOS per se ( 26 , 32 , 33 ), which was consistent with our outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a retrospective cross-sectional study involving Chinese with PCOS also discovered that the low level of 25OHD was prevalent in PCOS women ( 31 ). On the contrary, a systematic review and meta-analysis found that lower concentrations of serum 25OHD lead to a greater risk of developing PCOS ( 32 ). Besides, Panidis D et al.’s study grouped the patients with PCOS and controls according to BMI ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, symptomatology includes increased body weight and significant manifestations of depression or anxiety [ 4 ]. Deficiency of vitamin D has also been identified in PCOS patients, which may partly explain the hormonal and metabolic dysregulation seen in PCOS [ 5 ]. Vitamin D plays an important role in calcium homeostasis, which is crucial for the growth and development of young patients with PCOS [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 A significant number of women with polycystic ovary syndrome (PCOS) experience a deficiency in vitamin D. According to studies, between 67% and 85% of women with PCOS have low levels of 25-hydroxy vitamin D (25OHD), with concentrations below 20ng/ml. 8 Studies suggest that diminished quantities of 25OHD are connected to heightened insulin resistance, and administering vitamin D may ameliorate insulin resistance and insulin production in overweight females with polycystic ovary syndrome (PCOS). Moreover, insufficiency of vitamin D is correlated with disturbances in calcium levels, which may result in the halt of follicle development in females with PCOS.…”
Section: Introductionmentioning
confidence: 99%